Heterogeneity of Visual Preferences for Biological and Repetitive Movements in Children With Autism Spectrum Disorder. Issue 1 (21st September 2020) - Li, Tianbi; Li, Yewei; Hu, Yixiao; Wang, Yuyin; Lam, Cheuk Man; Ni, Wei; Wang, Xueqin; Yi, Li
Abstract : Previous studies have repeatedly reported atypical visual preferences to repetitive movements and deficient perception of biological movements in individuals with autism spectrum disorder (ASD). However, limited research has investigated the heterogeneity of the visual preferences in individuals with ASD. In the current study, we explored the visual preferences to different movement types (repetitive, biological, and random) in children with ASD using a paired preferential looking paradigm. Thirty‐nine children with ASD and 37 typically developing (TD) children participated in our study, with their eye movements recorded as the index of visual preferences. We examined the differences of visual preferences between the ASD and TD group, and the heterogeneity of visual preferences within the ASD group. We found group differences between children with ASD and TD children: Overall, the ASD group preferred repetitive movements while the TD group preferred biological movements. We also detected heterogeneity of visual preferences within the ASD group: Although the majority of children with ASD preferred repetitive movements as previous studies reported, 9 out of 39 children with ASD preferred biological movements similarly as their TD peers. Moreover, the visual preference patterns were correlated with autistic symptoms, especially the socio‐communicative impairments. Our study provided evidence of heterogeneity of visual attention and main visual preference to repetitive movements in children with ASD. The findings add to the body of literature of the heterogeneous behavioral symptoms and the atypical visual preferences in individuals with ASD. Lay Summary: The current study examined visual preferences to biological, repetitive, and random movements in children with Autism Spectrum Disorder (ASD). We showed a pair of two videos representing two types of movements (random, repetitive, or biological movements) to children with ASD and typically developing children. We found the main visual preferences for repetitive movements and heterogeneity of visual attention within the ASD group. Our findings provide theoretical and methodological implications for future study of the heterogeneity in the ASD population.